Annotated checklist to the vascular plant flora of Tuktut Nogait National Park and the Melville Hills region (Canadian Low Arctic) - Saarela, Jeffery M.; Gillespie, Lynn J.; Consaul, Laurie L.; Bull, Roger D. (Phytotaxa, 2013)
Tuktut Nogait National Park is located in the Melville Hills in the northeastern corner of mainland Northwest Territories in Canada's Southern Arctic Ecozone. The first major floristic survey of the Melville Hills region was conducted in 1990 as part of a natural resource inventory to determine its suitability as a National Park. We studied the flora and made extensive plant collections in Tuktut Nogait National Park and the Melville Hills region in 2009. Here, we present a comprehensive annotated checklist to the region's vascular plant flora based on a review of all existing and our own new collections. This includes the citation of all specimens examined, colour photographs for a subset of taxa and detailed taxonomic comments. The Melville Hills flora comprises 268 taxa (265 species and three additional infraspecific taxa), a 16% increase from the first survey, 215 of which are known from Tuktut Nogait National Park. Forty-eight taxa are newly recorded for the region and 54 taxa are newly recorded for Tuktut Nogait National Park. Noteworthy records include range extensions for Botrychium lunaria, Carex concinna, Draba borealis, Myriophyllum sibiricum, Plantago eriopoda, Poa alpina, Poa ammophila, Puccinellia banksiensis, Salix arbusculoides, and Selaginella selaginoides. The flora includes 19 vascular plant species of potential conservation concern in the Northwest Territories, including six assessed as "May Be At Risk", of which one occurs in the Park and 13 assessed as "Sensitive", of which eight occur in the Park.